A retrospective longitudinal study of adenovirus group F, norovirus GI and GII, rotavirus, and enterovirus nucleic acids in wastewater solids at two wastewater treatment plants: solid-liquid partitioning and relation to clinical testing data - Alexandria B. Boehm; Bridgette Shelden; Dorothea Duong; Niaz Banaei; Bradley J. White; Marlene K. Wolfe (mSphere, 2024)
ABSTRACTEnteric infections are important causes of morbidity and mortality, yet clinical surveillance is limited. Wastewater-based epidemiology (WBE) has been used to study community circulation of individual enteric viruses and panels of respiratory diseases, but there is limited work studying the concurrent circulation of a suite of important enteric viruses. A retrospective WBE study was carried out at two wastewater treatment plants located in California, United States. Using digital droplet polymerase chain reaction (PCR), we measured concentrations of human adenovirus group F, enteroviruses, norovirus genogroups I and II, and rotavirus nucleic acids in wastewater solids two times per week for 26 months (n = 459 samples) between February 2021 and mid-April 2023. A novel probe-based PCR assay was developed and validated for adenovirus. We compared viral nucleic acid concentrations to positivity rates for viral infections from clinical specimens submitted to a local clinical laboratory to assess concordance between the data sets. We detected all viral targets in wastewater solids. At both wastewater treatment plants, human adenovirus group F and norovirus GII nucleic acids were detected at the highest concentrations (median concentrations greater than 105 copies/g), while rotavirus RNA was detected at the lowest concentrations (median on the order of 103 copies/g). Rotavirus, adenovirus group F, and norovirus nucleic acid concentrations were positively associated with clinical specimen positivity rates. Concentrations of tested viral nucleic acids exhibited complex associations with SARS-CoV-2 and other respiratory viral nucleic acids in wastewater, suggesting divergent transmission patterns.IMPORTANCEThis study provides evidence for the use of wastewater solids for the sensitive detection of enteric virus targets in wastewater-based epidemiology programs aimed to better understand the spread of enteric disease at a localized, community level without limitations associated with testing many individuals. Wastewater data can inform clinical, public health, and individual decision-making aimed to reduce the transmission of enteric disease.